2005
DOI: 10.1093/ndt/gfh872
|View full text |Cite
|
Sign up to set email alerts
|

Role of atrophic changes in proximal tubular cells in the peritubular deposition of type IV collagen in a rat renal ablation model

Abstract: Background. Tubular atrophy, dilation and interstitial fibrosis are common in tubulointerstitial lesions, but the precise roles and inter-relationships of these components in the development of interstitial lesions have not been determined. This study focused on the origin and roles of atrophic tubules in the peritubular deposition of type IV collagen in a rat renal ablation model. Methods. Male Wistar rats underwent 5/6 nephrectomy or sham operation, and then were sacrificed at 4, 8 or 12 weeks, their remaini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 16 publications
1
22
0
Order By: Relevance
“…The present results may have clinical implications. As tubular apoptosis is detectable in various renal diseases [7][8][9][10][11][12][13][14] and tubular atrophy appears to be a better indicator of disease progression than glomerular pathology, 4,19,50,51 we postulate that RPTC apoptosis may be an initial step leading to tubular atrophy and that ROS is one of the key mediators of this process.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The present results may have clinical implications. As tubular apoptosis is detectable in various renal diseases [7][8][9][10][11][12][13][14] and tubular atrophy appears to be a better indicator of disease progression than glomerular pathology, 4,19,50,51 we postulate that RPTC apoptosis may be an initial step leading to tubular atrophy and that ROS is one of the key mediators of this process.…”
Section: Discussionmentioning
confidence: 98%
“…[1][2][3][4][5][6] Tubular atrophy has been observed in various experimental models of nephropathy as well as in human renal diseases, [7][8][9][10][11][12] including diabetic nephropathy. 13,14 However, the pathogenesis of tubular atrophy remains poorly understood.…”
mentioning
confidence: 99%
“…In some studies of renal disease models with fibrosis expression, α-SMA has been found in tubular cells, and that finding was considered as evidence for EMT (27)(28)(29). However, in most other studies α-SMA was exclusively found in interstitial cells around injured tubules, whereas the tubules themselves remained α-SMA-negative (15,17,19,(30)(31)(32)(33). The same observation was made in biopsies of patients with nephritic syndrome (34).…”
Section: Markers Of Emtmentioning
confidence: 90%
“…These dedifferentiated cells may produce bioactive molecules with autocrine and paracrine functions, which may have detrimental effects and potentiate fibrosis [4,15,16]. De Borst et al [17] reported that c-Jun NH 2 -terminal kinase (JNK) remained active in proximal tubule cells weeks after the ischemic insult and was associated with tubulointerstitial inflammation and fibrosis.…”
Section: How Does the Inability Of The Proximal Tubule Cell To Progrementioning
confidence: 99%